2007
DOI: 10.1152/ajplung.00360.2006
|View full text |Cite
|
Sign up to set email alerts
|

Roles of accumulated endogenous nitric oxide synthase inhibitors, enhanced arginase activity, and attenuated nitric oxide synthase activity in endothelial cells for pulmonary hypertension in rats

Abstract: Sasaki A, Doi S, Mizutani S, Azuma H. Roles of accumulated endogenous nitric oxide synthase inhibitors, enhanced arginase activity, and attenuated nitric oxide synthase activity in endothelial cells for pulmonary hypertension in rats. Am J Physiol Lung Cell Mol Physiol 292: L1480-L1487, 2007. First published February 23, 2007 doi:10.1152/ajplung.00360.2006 has been suggested to play a key role in the pathogenesis of pulmonary hypertension (PH). To determine which mechanism exists to affect NO production, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 49 publications
(59 reference statements)
2
44
0
Order By: Relevance
“…There are three distinct isoforms: NOS1, NOS2, and NOS3. Arginase competes with NOS for L-arginine under physiological conditions (61), and induction of arginase activity in the pulmonary circulation leads to a decrease in endothelial NO synthesis from NOS3 (48,63), a fundamental feature of many cardiovascular disorders. The proliferative and fibrotic effects of arginase activity may be further amplified by the competition of arginase I and NOS2 for L-arginine as substrate that restricts the generation of NO, which is an established inhibitor of SMC proliferation and collagen synthesis (17,30).…”
Section: Discussionmentioning
confidence: 99%
“…There are three distinct isoforms: NOS1, NOS2, and NOS3. Arginase competes with NOS for L-arginine under physiological conditions (61), and induction of arginase activity in the pulmonary circulation leads to a decrease in endothelial NO synthesis from NOS3 (48,63), a fundamental feature of many cardiovascular disorders. The proliferative and fibrotic effects of arginase activity may be further amplified by the competition of arginase I and NOS2 for L-arginine as substrate that restricts the generation of NO, which is an established inhibitor of SMC proliferation and collagen synthesis (17,30).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the enhanced arginase activity decreases L-arginine availability to NOS, thus impairing NO production (17). Enhanced arginase activity has been implicated in a number of conditions characterized by vascular dysfunction including pulmonary hypertension (18), intimal hyperplasia (19), agingassociated vascular dysfunction (20,21), and smokingrelated vascular dysfunction (22).…”
Section: Introductionmentioning
confidence: 99%
“…primary or secondary PH [22,[28][29][30][31][32]. To the best of our knowledge, our study is the first to have demonstrated the role of increased arginase activity in tobacco associatedpulmonary endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 54%